An Ontological Turn for Childhood Studies? - Spyrou, Spyros (Children & society, 2019)
The so‐called ‘ontological turn’ in the social sciences has brought with it yet another layer of theoretical concerns, except that this time the interest is in ontology rather than epistemology. New materialist thinking which has emerged in recent years promises to rethink the task of social theory in ways that circumvent modernist dualisms. In this paper, I explore what this might entail for childhood studies. What might such an ontological shift which emphasises among others relationality, connectedness and materiality mean for the further development of childhood studies? How would a decentring of children and the field's overpowering concerns for studying children's perspectives/voices/standpoints help rethink childhood studies and its remit? How, in short, would a shift from the child as an independent unit of analysis and of childhood as a categorical identity to a new ontology of emerging phenomena which implicate children, adults and non‐human forces affect the field's direction in the future?